Optimized design for time-of-flight total neutron scattering instrumentation using Monte Carlo simulations with application for the characterization of disordered macromolecules. Issue 4 (4th July 2019) - Han, Zehua; Zuo, Taisen; Ma, Changli; Cheng, He
Abstract: A time-of-flight neutron total scattering instrument for the China Spallation Neutron Source (CSNS) was designed. The instrument is designed for disordered macromolecular systems with characteristic lengths below 10 nm. The coupled hydrogen moderator of CSNS was selected to ensure the favorable statistics at the smallest scattering vector of 0.01 Å −1 . The optics and geometry of the instrument were optimized to cover a wide range of scattering vectors from 0.01 to 70 Å −1 . The performance of the instrument was examined using a series of Monte Carlo simulations, which demonstrate that the flux on the sample, the resolution, and the range of the scattering vectors are comparable to those of other advanced neutron total instruments. Finally, a virtual experiment was performed with silica powder. The resulting scattering pattern is consistent with both the numeric calculation and the estimated resolution of the instrument. The designed total scattering instrument at CSNS allows the simultaneous observation of both atomic and nanometer scale structures, having the potential to become a powerful tool for studying the structure of disordered materials in the fields of polymers, biology, and condensed matter physics.